2011
DOI: 10.1038/ng.978
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies new susceptibility loci for non-cardia gastric cancer at 3q13.31 and 5p13.1

Abstract: Gastric cancer, including the cardia and non-cardia types, is the second leading cause of cancer-related deaths worldwide. To identify genetic risk variants for non-cardia gastric cancer, we performed a genome-wide association study in 3,279 individuals (1,006 with non-cardia gastric cancer and 2,273 controls) of Chinese descent. We replicated significant associations in an additional 6,897 subjects (3,288 with non-cardia gastric cancer and 3,609 controls). We identified two new susceptibility loci for non-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
262
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(279 citation statements)
references
References 22 publications
11
262
0
3
Order By: Relevance
“…Recently, scientists found that PSCA gene is either abnormally expressed or shown different genetic variant in several cancers. GWAS have identified a strong association between PSCA gene rs2294008 C > T polymorphism and risk of GC, especially in Asians (Sakamoto et al, 2008;Shi et al, 2011 Qing-Hui Zhang*, Yong-Liang Yao, Tao Gu, Jin-Hua Gu, Ling Chen, Yun Liu and histological type of GC. More recently, several studies have assessed the relationship between the polymorphism of PSCA C > T and the susceptibility to GC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientists found that PSCA gene is either abnormally expressed or shown different genetic variant in several cancers. GWAS have identified a strong association between PSCA gene rs2294008 C > T polymorphism and risk of GC, especially in Asians (Sakamoto et al, 2008;Shi et al, 2011 Qing-Hui Zhang*, Yong-Liang Yao, Tao Gu, Jin-Hua Gu, Ling Chen, Yun Liu and histological type of GC. More recently, several studies have assessed the relationship between the polymorphism of PSCA C > T and the susceptibility to GC.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer risk SNPs were extracted from the original gastric cancer GWAS studies in GWAS Catalog 5, 6, 7, 8, 9, 10, 27. Only 1 SNP was remained when multiple variants were in linkage disequilibrium (LD, r 2  ≥ .8), and the minor‐allele frequency (MAF) should be greater or equal than .05.…”
Section: Methodsmentioning
confidence: 99%
“…Many genetic variations, most of which are single nucleotide polymorphisms (SNPs), have been detected over the past years by the genome‐wide association studies (GWAS) of gastric cancer 4. These common susceptibility loci included 1q22 ( MUC1 ), 3q13.32 ( ZBTB20 ), 5p13.1 ( PRKAA1 ), 5q14.3 ( lnc‐POLR3G‐4 ), 6p21.1 ( UNC5CL ), 8q24 ( PSCA ), and 10q23 ( PLCE1 ) 5, 6, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer includes non-cardia gastric and cardia gastric carcinoma. Two subtypes have differences in the etiology, pathology, carcinogenesis, and prognosis (Shi et al, 2011). So we restricted our cases to patients with non-cardia gastric cancer to supply relatively more homogeneous samples and improve the power of association study.…”
Section: Discussionmentioning
confidence: 99%